Carotid Dissection Associated with Ehlers-Danlos Syndrome. Report of One Case [Disección Carotídea en Paciente Con Síndrome de Ehlers-Danlos Tipo Vascular] - Chassin-Trubert-Contreras, A (2013)
In the vascular type of Ehlers-Danlos syndrome there is a defect in the synthesis of collagen type III, important constituent of the blood vessel wall, which may cause arterial rupture and dissection. We report a 15-year-old girl with a history of Ehlers- Danlos syndrome, who suffered an ischemic stroke secondary to dissection of the right internal carotid artery. She was managed conservatively with antiplatelet agents with a good clinical response.